Beyond the barricades: Social movements as participatory practice in health promotion. (January 2014) - Stephens, Christine
Community-based health promotion has focussed on empowering disadvantaged groups, but there is growing awareness of the need to address everyday practices used to maintain power and privilege across social divisions. Participatory Action Research projects have proved subject to problems of resistance from dominant social groups. Social movements seeking to reshape power relations, give voice to excluded people and promote a social environment in which their problems are understood have been suggested as an alternative approach. A model of social movements based on theories and observations of social movement dynamics offers a practical framework for initiating such social change.